Efficient Multi‐rate Encoder of QC‐LDPC Codes Based on FPGA for WIMAX Standard. Issue 2 (1st March 2017) - Wang, Xiumin; Ge, Tingting; Li, Jun; Su, Chen; Hong, Fangfei
Abstract : An efficient multi‐rate encoder for IEEE 802.16e LDPC codes which outperforms current single rate encoders with acceptable hardware consumption and efficient memory consumption is proposed. This design utilizes the common dual‐diagonal structure in parity matrices to avoid the inverse matrix operation which requires extensive computations. Parallel Matrix‐vector multiplication (MVM) units, bidirectional operation and storage compression are applied to this multi‐rate encoder to increase the encoding speed and significantly reduce the quantity of memory bits required. The proposed encoding architecture also contributes to the design of multi‐rate encoders whose parity matrices are dual‐diagonally structured and have an Approximately lower triangular (ALT) form, such as in IEEE 802.11n and IEEE 802.22. Simulation results verified that the proposed encoder can efficiently work for all code rates specified in WIMAX standard. With a maximum clock frequency of 117 MHz, the encoder achieves 3 to 10 times higher throughput than prior works. The proposed encoder is capable to switch among six rates by adjusting the input parameter and it achieves the throughput up to 1Gbps.